DETERMINATION OF MOSQUE QIBLA DIRECTION IN DARUSSALAM ACEH BESAR DISTRICT - Khalisil Mukhlis (SYARIAH: Journal of Islamic Law, 2020)
The problem of Qibla is nothing but a matter of direction, namely the direction of the Ka'bah in Makkah. The direction of the Ka'bah is determined from any point or place on the earth's surface by calculating and measuring. The calculation of the Qibla direction is basically intended to find out which direction the Ka'bah is seen from somewhere on the surface of the earth (azimuth). There are differences in the views of Dayah scholars in determining the direction of the Qibla prayer at mosques and Meunasah in Darussalam District, Aceh Besar Regency, such as the method of using a compass and guidelines for the setting sun. However, there are some people who do not want to accept the change in the direction of the Qibla. This has made many other people confused and anxious about this issue. This study used a qualitative method by collecting primary data in the form of interviews with Tengku-Tengku Dayah, Mosque/Meunasah imams, District MPU, Provincial BHR, and community leaders whom the authors consider to have knowledge of the direction of the Qibla in general. Secondary data is all documentation in the form of books, articles, journals, and other materials related to the object of research. The results showed that the views of Dayah Ulama were still very much accepted by the community, including in determining the direction of the Qibla. It is difficult to explain to the public about the importance of the accuracy of the Qibla direction if the results obtained are different from the accuracy of the previous Qibla direction. The development of technology has made the calculation of the Qibla direction more accurate. Even so, some people in Darussalam District still find it difficult to accept the change in the direction of the Qibla because they are still fanatical towards previous scholars, this has resulted in some people being reluctant, even unwilling to accept these changes. However, the number of people who received a change in the direction of the Qibla was greater, so that with the results of deliberation this problem could be resolved properly. The Azimuth of Darussalam Subdistrict based on the Provincial BHR measurement is 292º09 'from North to East moving clockwise.